Parenting, culture, and the development of externalizing behaviors from age 7 to 14 in nine countries - Jennifer E. Lansford (2018)
Copyright © Cambridge University Press 2018. Using multilevel models, we examined mother-, father-, and child-reported (N = 1,336 families) externalizing behavior problem trajectories from age 7 to 14 in nine countries (China, Colombia, Italy, Jordan, Kenya, the Philippines, Sweden, Thailand, and the United States). The intercept and slope of children's externalizing behavior trajectories varied both across individuals within culture and across cultures, and the variance was larger at the individual level than at the culture level. Mothers' and children's endorsement of aggression as well as mothers' authoritarian attitudes predicted higher age 8 intercepts of child externalizing behaviors. Furthermore, prediction from individual-level endorsement of aggression and authoritarian attitudes to more child externalizing behaviors was augmented by prediction from cultural-level endorsement of aggression and authoritarian attitudes, respectively. Cultures in which father-reported endorsement of aggression was higher and both mother- and father-reported authoritarian attitudes were higher also reported more child externalizing behavior problems at age 8. Among fathers, greater attributions regarding uncontrollable success in caregiving situations were associated with steeper declines in externalizing over time. Understanding cultural-level as well as individual-level correlates of children's externalizing behavior offers potential insights into prevention and intervention efforts that can be more effectively targeted at individual children and parents as well as targeted at changing cultural norms that increase the risk of children's and adolescents' externalizing behavior.